Effect of Crispy Catfish and Red Beans on Increasing the Hemoglobin Level of Young Women with Anemia - Hastuti, Widi; Eko Mulyo, Gurid Pramintarto; Aminah, Mimin; Widartika, Widartika; Assalam, Syarif; Amelia, Shilka; Nur Aeni, Muna (Gaceta Médica de Caracas, 2023)
Introduction: Women have the highest risk of suffering anemia, especially young women. One way to prevent anemia in adolescents is to increase the intake of food sources of protein and iron. One of the food sources of protein is catfish. Red beans as a vegetable source that contains iron and is high in fiber. Crispy catfish and red beans are food products that are processed, served attractively, and have a long shelf. The study aimed to determine the effect of crispy catfish and red beans on increasing hemoglobin (Hb) levels in young women with anemia.